Study on Soil-Water Characteristics of Expansive Soil under the Dry-Wet Cycle and Freeze-Thaw Cycle considering Volumetric Strain - Lisi Niu; Aijun Zhang; Jiamin Zhao; Wenyuan Ren; Yuguo Wang; Zhichao Liang (Advances in Civil Engineering)
This paper targets the expansive soils in Heilongjiang and Ankang to explore the influence of initial dry density, dry-wet cycle, and freeze-thaw cycle on the soil-water characteristics. The centrifuge method was used to obtain the soil-water characteristic curves (SWCCs) with different conditions. The volumetric strain of SWCC was modified based on the shrinkage test, and the corresponding fitting equations considering different factors were established. The results show that the volumetric water content is modified to consider the volume shrinkage effect of expansive soil, and the modification is more obvious in the high matric suction range. The smaller the initial dry density is, the worse the water-holding capacity of the sample is, and the smaller the air intake value is. The greater the time of the dry-wet cycle is, the greater the saturated volumetric water content of the sample is, and the corresponding water-holding capacity is significantly reduced. When the dry-wet cycle increases to a certain extent, the structure becomes stable. With the increase of the freeze-thaw cycle, the saturated volumetric water content first decreases and then increases. Similarly, after several times of the freeze-thaw cycle, the structure is basically stable. The fitted Gardner model equations under different conditions were proved to be able to describe the SWCCs of the two targeted expansive soils.